Pelaksanaan Kebijakan RTRW Mendukung Pembangunan Kawasan Strategis Ekonomi Oleh Dinas PUPR Sumbawa Barat - Erma Yulistiana; Lestari, Melly Aprilia; Purwadinata, Subhan (Nusantara: Jurnal Pengabdian kepada Masyarakat, 2025)
This devotion discusses the implementation of the Spatial Planning Policy (RTRW) in West Sumbawa Regency to support the development of strategic areas from an economic perspective. The RTRW policy serves as the foundation for the formulation of development programs, aiming to create efficient, effective, and sustainable land use. Using a descriptive qualitative research approach, this study highlights key factors in policy implementation, including communication, resources, disposition, and bureaucratic structure. The Results of dedication that although the RTRW policy has been implemented, various challenges remain, such as low public participation, limited human resources and budget constraints, and legal uncertainties in land use. Additionally, the complexity of the bureaucratic structure influences the effectiveness of RTRW policy implementation. This study emphasizes the need for improved communication between the government and the public, capacity building for human resources, and more balanced regulations to achieve sustainable development in West Sumbawa Regency.